Penerapan Landasan Filofis Bimbingan Dan Konseling Di SDN 1 Picungremuk - Destri Pusvita; Yayu Rahayu; Aura Nandira; Ayi Maulani; Aliya Rahmah; Fazar Satria Gumelar (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Education is a fundamental aspect of developing quality human resources. Guidance and counseling services play an integral role in addressing not only academic issues but also the personal, social, emotional, and moral development of students. This study aims to analyze the philosophical foundation underlying guidance and counseling policies and programs at SDN 1 Picungremuk, Tasikmalaya. Using a qualitative approach with structured interviews and observations, the study explored how these philosophical foundations are applied in the school environment. The findings highlight the importance of adopting a holistic approach in understanding and addressing students' academic, social, and emotional challenges. The study also emphasizes the collaboration between teachers and parents, the role of Ki Hajar Dewantara’s educational philosophy, and the integration of strategic steps in developing guidance and counseling programs. However, the challenges posed by digitalization require schools to balance the use of technology and the cultivation of social-emotional skills. Moving forward, the presence of professional counselors is recommended to enhance the effectiveness of the guidance and counseling program while allowing teachers to focus on their instructional responsibilities.